(3JYdjb GdaQGFO Ydi JSgjd GdahGFOs - (3eMeO Hf CHj HcQ Hf YeQ Hf CHj HcQ Hf eMeO, GdeNRhej GdbQTj, HOQ GdOjf GdeYQha HGHf GdOeGejfj , J (B827 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3ecI s)
(3ChdgG (B:s
(3JHJOF H` (B"(3HGH CaYd GdJaVjd(B" (3bhdg(B: (3bGd GdTGQM(B: (3MOg HYVge HCf bGd gh GdGSe GdeTJb GdehUha bGFe Hg eYfi djOd s
(3BNQgG (B:s
(3hjcJH jGA Ydi efGSHI MQcJgG, CVaJ, fMh ef NWjFI, Ch de JUa fMh ef GdcdG hgfG Je GdcJGH aj JYdjb GdaQGFO Ydi JSgjd GdahGFO s
(3HgG fXGe GdJYbjHIs
(3aj BNQgG PcQ GdfGSN Cfg cJHgG HSQYI hde jJecf ef eQGLYJgGs
(3aj GdUaMI GdCNjQI HYV GdJQGLes
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs